Population pharmacokinetic modelling to optimise treatment for children with Rifampicin-resistant TB and HIV - Van der Laan, Louvina Elizabeth (Department of Medicine, 2025)
The global burden of rifampicin- and/or multidrug-resistant (RR/MDR) -TB, i.e. Mycobacterium tuberculosis resistant to rifampicin and/or isoniazid is increasing, especially in settings with high HIV prevalence. Optimising the prevention and treatment of RR/MDR-TB in children in such settings is critically important. Population pharmacokinetic modelling, the state-of-the art technique to interpret pharmacological data, can play a pivotal role for therapeutic optimization in children, since it enables characterisation and inclusion of the effects of important developmental factors, thus allowing for determination and evaluation of effective yet safe RR/MDR treatment in children.